Study Group on Reforms in State Public Sector Undertakings Final Report Volume II - Planning Commission (Planning Commission, 2002)
A. P. State Financial Corporation, A. P. Handicraft Development Corporation Limited, A. P. Industrial Infrastructure Corporation Limited, A. P. Industrial Development Corporation Limited, Singareni Collieries Company Limited, Non-Conventional Energy Development Corporation of A. P. M, A. P. State Trading Corporation Limited. T&S, Nizam Sugar Factory, A. P. Technology Services, A. P. Foods
Planning Commission Government of India
Planning Commission Government of India